"Did Not Return in Time for Curfew": A Descriptive Analysis of Homeless Missing Persons Cases. (March 2023) - Huey, Laura; Ferguson, Lorna
Homeless communities have garnered recent public attention in Canada due to their high rates of violence, victimization, and being reported as missing. There have been several high-profile cases, investigations, and inquiries involving missing homeless persons, yet very little is known about what cases are reported to the police, under what circumstances they go missing, and the outcomes of those cases. As a result, the purpose of this study is to provide some insights into some of these unresolved issues by offering an exploratory, descriptive analysis of 291 closed missing person cases from the records of a municipal police service. What this analysis reveal is a somewhat more mundane picture. Specifically, results indicate that the majority of missing person reports are of those who are female and White, have a drug/alcohol addiction, are residing at homeless shelters/missions, and have a history of being reported as missing. As well, it was revealed that most people are reported as missing due to shelter/mission reporting issues with curfews and that all are located alive. This study extends the minimal existing scholarship on the missing homeless population by providing some preliminary insights on the vulnerabilities and factors that can impact these cases.